Assessment of Ultrasound as a Diagnostic Modality for Detecting Cervical Spine Fractures in Head-Injured Patients - Agrawal, Deepak; Sinha, Tej Prakash; Bhoi, Sanjeev (Indian Journal of Neurotrauma, 2015)
Background Early cervical spine clearance is extremely important in patients with head injuries and may be difficult to achieve in emergency setting. This is especially true in hemodynamically unstable unconscious patients and in low-resource settings.This study aimed to assess the feasibility of standard portable ultrasound in detecting cervical spine injuries in severe head-injured patients.Materials and Methods This retro-prospective pilot study performed over 1-month period (June–July 2013) after approval from the institutional ethics committee. During the study period the technique of cervical ultrasound was standardized by the authors and tested on 10 admitted patients of cervical spine injury. To assess feasibility in the emergency setting, hemodynamically stable patients with isolated severe head injury (GCS ≤8) coming to emergency department underwent ultrasound examination on a portable ultrasound machine (MicroMaxx, Sonosite Inc., Bothell, Washington, United States).Observations and Results Ultrasound examination of the cervical spine was possible in the emergency setting, even in unstable patients and could be done without moving the neck. The best window for the cervical spine was through the anterior triangle using the linear array probe (6–13 MHz). In the 10 patients with documented cervical spine injury, bilateral facet dislocation at C5–6 was seen in four patients and at C6–7 was seen in three patients. C5 burst fracture was present in one and C2 anterolisthesis was seen in one patient. Cervical ultrasound could easily detect fracture lines, canal compromise, and ligament injury in all cases.Conclusion Cervical ultrasound may be a useful tool for detecting cervical spine injury in unconscious patients, especially those who are hemodynamically unstable. It may be particularly useful in the resource-constrained setting of developing countries
Keywords: ultrasound; cervical injury; head injury; cervical spine clearance